2016
DOI: 10.2147/ndt.s109954
|View full text |Cite
|
Sign up to set email alerts
|

Higher minor hemoglobin A2 levels in multiple sclerosis patients correlate with lesser disease severity

Abstract: Objective To define whether minor adult hemoglobin A2 (HbA2, α2δ2) exerts any protective activity in multiple sclerosis (MS). Methods HbA2 levels were measured in 146 MS patients with high performance liquid chromatography and association with MS Severity Scores (MSSS) were determined. HbA2 associations with blood count parameters were also studied using blood counts evaluated on the same day of high performance liquid chromatography sampling. Routine biochemical parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 32 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…It has been reported that multiple sclerosis patients treated with IFNb have higher levels of HbA2 in comparison to those treated with other drugs (26). For the purpose of verifying whether therapy with IFNb was the cause of the increase in HbA2 in vivo, we performed a study in MS patients.…”
Section: Hemoglobin A2 Levels Increase After Ifnb Treatments In Multimentioning
confidence: 99%
“…It has been reported that multiple sclerosis patients treated with IFNb have higher levels of HbA2 in comparison to those treated with other drugs (26). For the purpose of verifying whether therapy with IFNb was the cause of the increase in HbA2 in vivo, we performed a study in MS patients.…”
Section: Hemoglobin A2 Levels Increase After Ifnb Treatments In Multimentioning
confidence: 99%